Modelling of the canopy photosynthesis in intercropping with lettuce, rocket, radish, coriander and red beet - Paiva, Laíza Gomes de; Costa, Caciana Cavalcanti; Cavalcante, Jerfferson Araujo; Lopes, Kilson Pinheiro; Barbosa, José Wilson da Silva (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2016)
In the past years, many combinations of plants in intercropping have been demonstrating agronomic viability due to the increase of production per unity of area and greater use of natural resources. However, the knowledge and the proper choice of crops that will be part of the system are necessary to reach achievement, so that there is mutual interaction between them. The study had the purpose of evaluate the productivity of lettuce (Elba) intercropped with coriander (Verdão), rocket (Cultivada), beet (Early Wonder) or radish (Crimson Gigante). The experiment was conducted in the experimental area of the CCTA/UFCG, Pombal/PB, from September 2013 to July 2014. Nine treatments were assessed (4 intercropping and 5 monocultures), installed in randomized blocks with four replications. The amalgamation of lettuce with crops of coriander, rocket, radish or beet did not affected negatively its profitability. The intercropping of lettuce and beet presented the greater productive efficiency and efficient use of land, demonstrated by the increased production of both crops in this association. Modelagem do dossel fotossintético em sistemas consorciados com alface, rúcula, rabanete, coentro e beterraba Resumo: Nos últimos anos muitas combinações de plantas em cultivo consorciado têm demonstrado viabilidade agronômica devido ao aumento de produção por unidade de área e maior aproveitamento de recursos naturais, no entanto, para que esse sistema alcance sucesso é necessário a escolha adequada das culturas que irão fazer parte do mesmo, de maneira que haja interação mútua entre elas. Com o objetivo de avaliar a produtividade da cultura da alface (‘Elba’) em consórcio com coentro (‘Verdão’), rúcula (‘Cultivada’), rabanete (‘Crimson Gigante’), or beterraba (‘Early Wonder’) foi realizado o experimento na área experimental do CCTA/UFCG, em Pombal, PB, no período de setembro de 2013 a julho de 2014. Foram avaliados 9 tratamentos (4 cultivos consórcios e cinco monocultivos), instalados em blocos casualizados, com quatro repetições. A combinação da alface com as culturas do coentro, rúcula, rabanete ou beterraba não afetou negativamente a sua rentabilidade. O consórcio de alface e beterraba foi o que apresentou o seu maior rendimento produtivo e de uso eficiente da terra, demonstrado pelo aumento da produção de ambas as culturas, nesta associação.